JURIDICAL ANALYSIS OF THE USE OF CRYPTOCURRENCY (CRYPTO ASSETS) AS A MEANS OF MONEY LAUNDERING AND ITS HANDLING BASED ON THE REGULATIONS OF THE COMMODITY FUTURES TRADING SUPERVISORY AGENCY (BAPPEBTI) NO.5 AND NO.6 OF 2019 - Achmad Kamal Mansur Siregar; Sunarmi; Robert (Talenta Publisher, 2025)
The development of financial technology has given rise to Cryptocurrency as a popular form of digital asset in various parts of the world, including Indonesia. Its decentralized nature, high anonymity, and ease of cross-border transactions make Cryptocurrency an instrument vulnerable to misuse, including as a means of money laundering (TPPU). This study aims to: (1) analyze the legal provisions governing the prohibition of Cryptocurrency as a means of money laundering; (2) assess the extent to which Indonesian positive law, specifically BAPPEBTI Regulation No. 5 of 2019 and BAPPEBTI Regulation No. 6 of 2019, is adequate in preventing crypto misuse; and (3) identify strategies for prevention, supervision, and enforcement against crypto-based money laundering practices in Indonesia. The research method used is normative legal research with a juridical-descriptive approach. The research data was obtained from primary legal materials in the form of laws and court decisions, as well as secondary legal materials in the form of legal literature, scientific journals, official agency reports, and actual case studies. The analysis was conducted qualitatively by interpreting and examining the alignment between legal norms and field practices. The results show that although BAPPEBTI Regulations No. 5 and No. 6 of 2019 provide a legal basis for regulating the trading of crypto assets as digital commodities, these regulations still focus more on the technical aspects of trading and asset registration, rather than on preventing money laundering. This indicates that national legal instruments still have weaknesses in terms of enforcement, inter-agency coordination, human resource capacity, and international cooperation.